Revised adult T-cell Leukemia-Lymphoma international consensus meeting report - Cook,LB; Fuji,S; Hermine,O; Bazarbachi,A; Ramos,JC; Ratner,L; Horwitz,S; Fields,P; Tanase,A; Bumbea,H; Cwynarski,K; Taylor,G; et al. (Journal of Clinical Oncology, 2019)
PURPOSE: Adult T-cell leukemia-lymphoma (ATL) is a distinct mature T-cell malignancy caused by chronic infection with human T-lymphotropic virus type 1 with diverse clinical features and prognosis. ATL remains a challenging disease as a result of its diverse clinical features, multidrug resistance of malignant cells, frequent large tumor burden, hypercalcemia, and/or frequent opportunistic infection. In 2009, we published a consensus report to define prognostic factors, clinical subclassifications, treatment strategies, and response criteria. The 2009 consensus report has become the standard reference for clinical trials in ATL and a guide for clinical management. Since the last consensus there has been progress in the understanding of the molecular pathophysiology of ATL and risk-adapted treatment approaches. METHODS: Reflecting these advances, ATL researchers and clinicians joined together at the 18th International Conference on Human Retrovirology-Human T-Lymphotropic Virus and Related Retroviruses-in Tokyo, Japan, March, 2017, to review evidence for current clinical practice and to update the consensus with a new focus on the subtype classification of cutaneous ATL, CNS lesions in aggressive ATL, management of elderly or transplantation-ineligible patients, and treatment strategies that incorporate up-front allogeneic hematopoietic stem-cell transplantation and novel agents. RESULTS: As a result of lower-quality clinical evidence, a best practice approach was adopted and consensus statements agreed on by coauthors (> 90% agreement). CONCLUSION: This expert consensus highlights the need for additional clinical trials to develop novel standard therapies for the treatment of ATL.